Lessons learned from the aerodynamic shape development process of a bobsleigh - Pernpeintner, A.; Winkler, A. (Procedia Engineering, 2010)
Experiences made with the systematic aerodynamic development process of a bobsleigh are presented. The challenges and the potentials of the preliminary design phase and of the detail optimization phase are discussed. It is demonstrated that the appropriate application of the tools and methods leads to a considerable increase in the product quality. The challenges that arise from field testing under unfavourable weather conditions are addressed.